Reduction of Radiation Dose Received by Surgeons and Patients During Percutaneous Nephrolithotomy: A New Shielding Method - Amirhasani, Shahriar; Daneshdoost, Rezgar; Mousavibahar, Seyedhabibollah; Ghazikhanlou-sani, Karim; Raeisi, Roya (Urology Journal, 2021)
Purpose: Due to high prevalence of urolithiasis, endourologic interventions have increased for the treatment of patients with urinary stones. During fluoroscopy-guided percutaneous nephrolithotomy (PCNL), the surgeon and the patient are exposed to X-ray and its harmful effects. This study aimed to assess the reduction of the radiation dose received by surgeons and patients after using a new shielding method. Materials and Methods: In this study, the dose of radiation exposure by the surgeon and patient during PCNL under fluoroscopic procedure with conventional shielding methods was compared to a new shielding method designed by the researcher. For this purpose, shields and lead cones with a thickness of 0.5 mm were used. Also, to evaluate the dose of radiation received by surgeons and patients in different parts of the body, thermoluminescent dosimeters (TLD) were used. Results: By using the new shielding method, a 37 ± 2% reduction was found in the dose exposure as compared to the conventional shielding method. The maximum reduction in radiation dose was specified to the surgeon’s hands, while the lowest reduction in radiation dose was related to the surgeon’s thyroid gland. The maximum and minimum reductions in radiation exposure for patients were specified to patients’ feet and chest respectively. Conclusion: There is a significant difference between the total dose received by the surgeons and the patients following the use of the new shielding method and the standard shielding method. The new shielding method can reduce 37 ± 2% of the x-ray received by the patient and the surgeon during fluoroscopy-guided PCNL.